Study of nitrogen pollution in the Republic of North Macedonia by moss biomonitoring and Kjeldahl method - Trajče Stafilov, Zdravko Špirić, Marin Glad, Lambe Barandovski, Katerina Bačeva Andonovska, Robert Šajn, Oleg Antonić (Taylor and Francis, 2020)
In the summer of 2005 and 2010, moss samples were collected from 72 sampling sites evenly distributed all over the territory of Republic of North Macedonia. Kjeldahl method was used to determine the nitrogen content in the samples. Descriptive statistics and distribution maps were prepared. Data obtained from these two surveys were compared, and additional comparison was done with data obtained from similar studies in the South-Eastern European countries and Finland as a clean area. The median value of N content in the samples collected in 2005 is 1.21%, varies from 0.70% to 1.54%, while the content of N in samples collected in 2010 ranges between 0.68% and 1.75% with the median value of 1.06%. High contents of N were found in the Northern and Central parts of the country mainly as a result of agricultural activities, industry and traffic.
Keywords: Kjeldahl method; Nitrogen; North Macedonia; air pollution; moss biomonitoring.